| **Giver** | **Post** | **Date** |

| kh2542 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 02-Oct-2021 |

| PangKj | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 01-Oct-2021 |

| Panshock | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 19-Sep-2021 |

| sharanyasri | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 16-Sep-2021 |

| rahuly2k2001 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-Sep-2021 |

| tranthanhbinh | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 02-Sep-2021 |

| salaah | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 22-Aug-2021 |

| rohit03 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Aug-2021 |

| Ruby12 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 02-Aug-2021 |

| JadAsmar | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 29-Jul-2021 |

| RemyBoy | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 29-Jun-2021 |

| Uditb | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 22-Jun-2021 |

| Chasingthesun | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 14-Jun-2021 |

| Nyssa | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 13-Jun-2021 |

| minhhuy26107 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 12-Jun-2021 |

| Asitima | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Jun-2021 |

| Ars96 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 11-Jun-2021 |

| ad2210 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-Jun-2021 |

| DIPU226 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 07-Jun-2021 |

| RishabhJha | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Jun-2021 |

| scratch12 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 28-May-2021 |

| mohitdewan | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 27-May-2021 |

| JaisonDsouza | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 15-May-2021 |

| RR1996 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 10-May-2021 |

| tasbir4165 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 23-Apr-2021 |

| Apsteu | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 22-Apr-2021 |

| hrishi760 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 20-Apr-2021 |

| pragyak9 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Apr-2021 |

| arjita42 | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 06-Apr-2021 |

| YellowPowerRanger | If a, b, and c are constants, a > b > c, and x^3 - x = (x - a)(x - b) | 05-Apr-2021 |